2021
DOI: 10.1101/2021.06.14.21258762
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Non-replication of structural brain changes from Mindfulness-Based Stress Reduction: Two combined randomized controlled trials

Abstract: Studies purporting to show changes in brain structure following the popular, eight-week Mindfulness-Based Stress Reduction (MBSR) course are widely referenced despite major methodological limitations. Here, we present findings from a large, combined dataset of two, three-arm randomized controlled trials with active and waitlist (WL) control groups. Meditation-naive participants (n=218) completed structural MRI scans during two visits: baseline and post-intervention period. After baseline, participants were ran… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 56 publications
3
15
2
Order By: Relevance
“…Note. Introjected motivation is featured in this figure, but was not differentiated empirically from identified motivation in the present study reduction) has found that a minimum of 27 h of practice time is needed for a change in amygdala volume (Kral et al, 2022). These findings indicate larger neuronal changes for longer mindfulness interventions compared to only brief mindfulness interventions.…”
contrasting
confidence: 48%
See 1 more Smart Citation
“…Note. Introjected motivation is featured in this figure, but was not differentiated empirically from identified motivation in the present study reduction) has found that a minimum of 27 h of practice time is needed for a change in amygdala volume (Kral et al, 2022). These findings indicate larger neuronal changes for longer mindfulness interventions compared to only brief mindfulness interventions.…”
contrasting
confidence: 48%
“…There is some evidence that even brief mindfulness interventions are sufficient to achieve a state of mindfulness that affects brain activity as well as cognition and feelings (Medvedev et al, 2017 ). On the other hand, recent research on MBSR (mindfulness-based stress reduction) has found that a minimum of 27 h of practice time is needed for a change in amygdala volume (Kral et al, 2022 ). These findings indicate larger neuronal changes for longer mindfulness interventions compared to only brief mindfulness interventions.…”
mentioning
confidence: 99%
“…The inclusion of active controls is important in what concerns study design namely because it helps to solve the question of double-blinding ( Davidson and Kaszniak, 2015 ). A recent study analyzed the effects of including a validated well-matched active control group with a large sample size and defined in a randomized manner in the effects of MBSR in brain structure ( Kral et al, 2022 ). This study failed to confirm previous results showing neuroplastic changes induced by MBSR groups in comparison to active controls, which reinforces the importance of defining the best control groups for each MBI intervention which may probably require both active and waiting list groups ( Kral et al, 2022 ).…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…A recent study analyzed the effects of including a validated well-matched active control group with a large sample size and defined in a randomized manner in the effects of MBSR in brain structure ( Kral et al, 2022 ). This study failed to confirm previous results showing neuroplastic changes induced by MBSR groups in comparison to active controls, which reinforces the importance of defining the best control groups for each MBI intervention which may probably require both active and waiting list groups ( Kral et al, 2022 ). As to fibromyalgia, it was never evaluated the importance of defining control groups in MBI research.…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…Neuroimaging evidence shows that MM might induce neuroplastic changes in the structure and the function of brain regions involved in attentional processes, memory, emotion regulation, self-awareness, exteroceptive and interoceptive body awareness, and self-control (Fox et al, 2014;Tang et al, 2015; but see Kral et al, 2022 for a different view). Other meditation practices include loving-kindness meditation (LKM, aimed at developing positive emotions toward oneself and others) and compassion meditation (CM, aimed at cultivating compassion toward others) (Hofmann et al, 2011).…”
Section: Introductionmentioning
confidence: 99%